AN ANALYSIS OF IMPLEMENTATION OF FOOD SAFETY MANAGEMENT ISO 22000:2005 AT PT AERO PRIMA FOOD SERVICE SURAKARTA - Budiyono Budiyono (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
The purpose of this study was to determine the effect of implementing SMKP ISO 22000:2005 on Organizational Performance at PT. Aero Prima Food Services. Organizational Performance is measured by the implementation of the Basic Eligibility Requirements Program, HACCP principles, and Interactive Communication. The research data uses primary data by distributing questionnaires to correspondents, namely employees of PT. Aero Prima Food Services. The data collection technique uses the Purpose Sampling technique. The independent variables of this study are the Basic Eligibility Requirements Program, HACCP Principles, and Interactive Communication, while the dependent variable is Organizational Performance. The data analysis method used in this research is Descriptive Statistics, Validity Test, and Reliability Test. For the hypothesis analysis method using Multiple Linear Regression Analysis, namely the Partial Test (t test), Simultaneous Test (F test) and Coefficient of Determination (Adjusted R Square). The results showed that the Basic Feasibility Requirements Program (PPD) had a significant effect on Organizational Performance of 0.000, smaller than the significance level of 0.05 (0.000 < 0.05), the HACCP Principle had a significant effect on Organizational Performance of 0.000, which was smaller than the significance level, namely 0.05 (0.000